Bankruptcy And Its Effect On Corporate Hedging - Ika Yoga (AIBPM Publisher, 2019)
Corporate hedging is basically an effort of the companies to protect their values which has an impact on the shareholders’ welfare. This study aims at examining and analyzing the variable bankruptcy of the companies and their effects on Islamic corporate hedging conducted by Islamic commercial banks in Indonesia. The bankruptcy variable in this study uses the Grover G Score model represented by the variable ratio: (1) net working capital to total assets, (2) earnings before interest and tax to total assets and (3) return on assets (ROA), while the corporate hedging is meassured by utilizing dummy variables. The finding of logistical regresion analysis reveals that all variables used in bankruptcy assessment had a significant influence on corporate hedging decisions.